A Multiple Case Study of Latina Breast Cancer Survivors Returning to Work With Breast Cancer-Related Lymphedema: Adaptation, Resilience, and Quality of Life. (December 2022) - Anderson, Elizabeth A; Anbari, Allison B; Sun, Yuanlu; Armer, Jane M
Introduction: Breast cancer-related lymphedema (BCRL), a side effect of cancer treatment, may negatively impact the ability to perform work. Factors such as delayed diagnosis, late-stage disease, and a high percentage of service occupations may challenge work choices for Latinas after BCRL diagnosis.Methods: Our multiple case study explored work experiences and quality of life (QOL) for Hispanic/Latina survivors. Participants completed demographic and short form-36 (SF-36) surveys. Semi-structured interviews focused on how work environment, self-management, and QOL were influenced by BCRL. Thematic analysis of cases used In Vivo and descriptive coding and constant cross-case comparative methods.Results: Analysis illustrated how Hispanic/Latina survivors perceive the influence of BCRL on work experience as requiring adaptation and personal resilience. Participants identified BCRL knowledge gap challenges and described coping with physical, psychosocial, and work activity changes. They described creative work adaptations and discussed BCRL's impact on both positive and negative interpersonal perceptions. Strong support from family, friends, and colleagues contributed to improved QOL and continued work activities.Conclusion: Future research should incorporate coping strategies and creative management of BCRL to optimize work activities across the lifespan. These strategies can provide guidance for the creation of survivorship care plans, education of healthcare professionals (HCPs), and lifelong occupational support.